Gastronomic Curiosities from the Periphery of the Turkic Speaking World - Elisabetta Ragagnin (2020)
This contribution offers gastronomic and etymological insights from distant corners of the Turkic speaking world, namely from Mongolia’s Khövsgöl region. Mongolia’s north-western corners of Khövsgöl region, bordering with the Tuvan Republic and Buriatia, are home of the Dukhan people, who follow a unique lifestyle centred on the herding of reindeer. Linguistically, Dukhan belongs to Taiga-Sayan Turkic, a subgroup of the Siberian branch of the Turkic languages family. On the lexical level, Dukhan includes a substantial amount of loans from Mongolic varieties and a limited number of Russian and Samoyedic loanwords.